Morphological aspects of growth and production of black pepper cultivars in a sustainable tutor of gliricidia in the Baixo Tocantins mesoregion – Pará - Lemos, Oriel Filgueira de (2022)
Culturally, the wooden stake is used for the cultivation of black pepper in the field, however, the gliricidia tutor has emerged as a sustainable and viable alternative for use in the production system of the species. Despite the reduction in costs for the implementation of pepper plants, there is little adoption of the technology by the farmer, due to the scarcity of information on the behavior of cultivars. In order to evaluate cultivars under morphological aspects of growth and production in live tutor of gliricidia, compared to the dead tutor, a case study was carried out installing an experiment in a producer area in Baião - PA in DBC with five cultivars and five replications considering four plants/cultivar. Plant height, stem diameter and number of orthotropic branches were taken at 12 months, as well as petiole length, width, length and thickness of dult leaves, as well as size, weight and number of fruits/spike, submitted to ANOVA and Tukey test at 5%. Cultivar Kuthiravally showed the highest average for Number of Orthotropic Branches in both types of tutors. Bragantina, Clonada and Cingapore showed greater petiole lengths in live tutor, and Bragantina and Uthirankotta showed larger spike when cultivated in gliricidia. Therefore, there is an influence of the type of tutor on the morphological characters of growth and production of cultivars of this species, indicating the possibility of successfully using gliricidia in the field.